حماية المستهلك من الإجبار عن التعاقد في التشريع الجزائري - عميرات, عادل (revue mofakir, 2018)
Ban legislator all behavior can be exercised by economic help to the consumer receives from his will and make them defective unable to contract as a free and healthy, do not accept the contract chosen, but forced under the influence of illegal practices to aid the economic but it was directly or indirectly, and the most important of these practices addressed by the legislature urban areas because of its negative impact on the consumer and the economy in general mention of deception and fraud and monopoly.